Generation of dopaminergic neurons by fusion of neural stem cells and midbrain neurons - Yu, Y.; Wen, T. (Cellular and Molecular Biology, 2011)
Neural stem cells (NSCs) are multipotent and self-renewing that can potentially generate various neurons for clinical purposes. However, the mechanism of regulating differentiation from NSCs to neurons is not well understood. In this report, we established a new method to obtain specific neurons from NSCs by cell fusion. NSCs were fused with midbrain neurons, resulting in hybrid cells that express an antigen pattern characteristic of dopaminergic neurons. Analysis of the marker enzyme tyrosine hydroxylase (TH) showed that hybrid cells were reprogrammed to somatic cells. This report represents a new significant contribution toward revealing the directional differentiation of NSCs and eventually providing the application in clinical transplantation therapy.